The Lisa Bach Case - Anonymous (Online Ethics Center, 2006)
This case discusses issues of post-doc mentor/student relationships, intellectual property, publication, credit, authorship and collaboration.
Case Study / Scenario|Hypothetical / Fictional Case
Keywords: Authorship; Collaboration; Mentors and Trainees; Publication Ethics; Research and Practice